Applications of bio-cementation and bio-polymerization for aeolian erosion control. (April 2021) - Devrani, Rituraj; Dubey, Anant Aishwarya; Ravi, K.; Sahoo, Lingaraj
Abstract: This study investigates soil stabilization through two soil strengthening techniques, specifically; Bio-cementation through Microbial induced calcite precipitation (MICP) and Bio-polymerization using Xanthan gum for aeolian erosion control applications. The performances of these techniques were evaluated in terms of improvement in Threshold friction velocity (TFV), soil mass loss (%), and soil crust thickness formed with different levels of the treatment by conducting a series of experiments in the laboratory-scale wind tunnel and the microstructural observations with the help of FESEM and X-ray diffraction techniques. The results from wind erosion studies exhibited an improvement in TFV from 20 km/h for untreated to 45 km/h for MICP and biopolymer treated sand. A reduction in the soil mass loss from 75.23% for untreated to as least as 0% with both MICP and biopolymer treatment was observed. The results also indicated that the concentration of urea-cacl2 and biopolymer both played a critical role in soil improvement in both treatment methods. In MICP treated soil, the maximum wind speed of 45 km/h was encountered as TFV with 0.5M urea-cacl2 . Whereas the TFV of biopolymer treated soil encountered the maximum wind speed of 45 km/h with a minimum of 0.25% of Xanthan Gum biopolymer solution. Highlights: Application of bio-cementation and bio-polymerization for aeolian erosion control is presented. Bio-cementation was achieved through MICP using Bacillus megaterium and Bio-polymerization was achieved using Xanthan gum. Erosion mitigation of soil was quantified by measuring Threshold friction velocity, soil mass loss (%), and soil crust thickness. FESEM and XRD patterns reveal changes in the pore network and soil mineralogy after both the treatment in soil. Bio-cementation and Bio-polymerization was found as a promising solution for erosion control in arid and semi-arid regions.